Bad habits-good goals?: Meta-analysis and translation of the habit construct to alcoholism - Giannone, Francesco; Ebrahimi, C.; Endrass, T.; Hansson, Anita C.; Schlagenhauf, F.; Sommer, Wolfgang H. (Translational Psychiatry, 2024)
Excessive alcohol consumption remains a global public health crisis, with millions suffering from alcohol use disorder (AUD, or simply “alcoholism”), leading to significantly reduced life expectancy. This review examines the interplay between habitual and goal-directed behaviors and the associated neurobiological changes induced by chronic alcohol exposure. Contrary to a strict habit-goal dichotomy, our meta-analysis of the published animal experiments combined with a review of human studies reveals a nuanced transition between these behavioral control systems, emphasizing the need for refined terminology to capture the probabilistic nature of decision biases in individuals with a history of chronic alcohol exposure. Furthermore, we distinguish habitual responding from compulsivity, viewing them as separate entities with diverse roles throughout the stages of the addiction cycle. By addressing species-specific differences and translational challenges in habit research, we provide insights to enhance future investigations and inform strategies for combatting AUD.